Pengaruh Inflasi, Suku Bunga As, Harga Emas, Harga Minyak Bumi, Inflasi As Dan Kurs Rupiah Terhadap Indeks Sektoral Di Indonesia - Sylvin Antonius (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This thesis created to study the effect from each macro variable from Dow Jones Index, US Interest Rate, Price of Gold, Price of Oil, US Inflation and Rupiah Exchange Rate to Sectoral Indicies and help investors to make a better decision for investors in investing. The timeline of the data for this study will start from 2014 to 2016 where some changes will be seen in US Interest Rate. The analysis method that will be used in this study will be regression where a different assumption can be made even though a lot of previous study results in significancy with IHSG. Finally, not all data show significancy when compared to each sector from Sectoral Indicies. This fact can be checked from the significance from doing T test from Eviews9. Assumption that can be seen here is that macro data such as Dow Jones Index got high significancy with Sectoral Indicies while others are lower.